Strategic Selenium Application Methods and Timing Enhance Grain Yield, Minimize Cadmium Bioaccumulation, and Optimize Selenium Fortification in Triticum aestivum L. - Dazhong Zhang; Jiajia Liu; Tingting Cheng; Hongyi Wang; Yongzhen Zhou; Zhengwu Gong; Tiezhu Hu (Agronomy)
Based on previous research, we hypothesized that an SeVI and SeMet combined application at different growth stages could increase the yield and Se concentration and decrease Cd concentration in wheat grains. To verify this hypothesis, we designed a pot experiment throughout the wheat growth period and investigated the effects of SeIV, SeVI, and SeMet applied individually or in combination at different growth stages on yield traits; Cd absorption and transport; and Se content under Cd stress. The results indicated that grain yield was the highest under the SeVI individual application treatment and the SeVI (at the seedling, jointing, and heading stages) and SeMet (at the filling stage) combined application treatment (3 + 1 treatment), showing a more than 42% increase compared with the Cd-only control treatment (CK). Under the 5 mg/kg Cd stress, the grain Cd content in the 3 + 1 treatment was 34.1% lower than that in CK and over 14.1% lower than those in Se individual treatments. Furthermore, grain Se content was the highest under the 3 + 1 treatment, being 160.8%, 99.7%, and 39.5% higher than those in the SeIV, SeVI, and SeMet individual treatments under 5 mg/kg Cd stress. This may be attributed to early SeVI application in the 3 + 1 treatment, which enhanced yield traits and effectively promoted the retention of Cd in the middle and lower organs, reducing its transport to the grains. Furthermore, the SeMet application enhanced Se translocation to the grains, further reducing Cd content and increasing the Se concentration. In conclusion, the combined application of SeVI (at the seedling, jointing, and heading stages) and SeMet (at the filling stage) helped achieve the desired outcomes of high grain yield, low Cd content, and Se enrichment under Cd stress.